2022
DOI: 10.1108/ejmbe-12-2021-0343
|View full text |Cite
|
Sign up to set email alerts
|

Human resource development and turnover intention: organizational commitment's role as a mediating variable

Abstract: PurposeThe purpose of this paper is to examine the effect of human resource development on turnover intention through the mediating role of organizational commitment.Design/methodology/approachThis paper used a quantitative research design. Data were collected from 204 flight attendants employees working at Royal Jordanian Airlines Company using an email survey questionnaire. Structural equation modeling (SEM) was adopted to test the hypothesized model.FindingsThe results assure positive effect of human resour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…In this study, we controlled for work organization conditions, sociodemographic factors, and the stress related to the COVID-19 pandemic. Literature demonstrated that work organization conditions can influence job performance (Simard and Parent-Lamarche, 2021;Rawashdeh et al, 2022). They encompassed five work-related variables, which can affect job performance: workload (Bruggen, 2015;Parent-Lamarche and Boulet, 2021b); skill utilization and decision authority (Simard and Parent-Lamarche, 2021;Hackman and Oldham, 1980), as well as recognition Oldham, 1976, 1980;Ahmad et al, 2017;Bradler et al, 2016;Parent-Lamarche and Laforce, 2022), and job insecurity (Sverke et al, 2002;Kalia and Bhardwaj, 2019;Begum et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we controlled for work organization conditions, sociodemographic factors, and the stress related to the COVID-19 pandemic. Literature demonstrated that work organization conditions can influence job performance (Simard and Parent-Lamarche, 2021;Rawashdeh et al, 2022). They encompassed five work-related variables, which can affect job performance: workload (Bruggen, 2015;Parent-Lamarche and Boulet, 2021b); skill utilization and decision authority (Simard and Parent-Lamarche, 2021;Hackman and Oldham, 1980), as well as recognition Oldham, 1976, 1980;Ahmad et al, 2017;Bradler et al, 2016;Parent-Lamarche and Laforce, 2022), and job insecurity (Sverke et al, 2002;Kalia and Bhardwaj, 2019;Begum et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we controlled for work organization conditions, sociodemographic factors, and the stress related to the COVID-19 pandemic. Literature demonstrated that work organization conditions can influence job performance (Simard and Parent-Lamarche, 2021; Rawashdeh et al. , 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, employees with higher level of engagement or commitment are less likely to have turnover intention (Bhatnagar, 2012;Rich et al, 2010). Empirical studies confirm the positive effects of engagement on satisfaction and retention among employees (Mazzetti et al, 2021;Alola and Alafeshat, 2021;Memon et al, 2016;Bakker and Demerouti, 2008;Rawashdeh et al, 2021). Accordingly, we propose the following hypotheses: H4.…”
Section: Employee Engagement Satisfaction and Retentionmentioning
confidence: 71%
“…Career development is also important to help employees determine career-related goals, improve appropriate skills and knowledge and understand personal objectives, thereby increasing their work motivation and satisfaction (Huang and Su, 2016;Nankervis et al, 2014;Amin et al, 2014;Rogers and Creed, 2011;Dysvik and Kuvaas, 2008;Chen et al, 2004). Literature documents that TD is positively associated with ES and ER (Rawashdeh et al, 2021;Aburumman et al, 2020;Bibi et al, 2018;Memon et al, 2016;Fletcher et al, 2018;Sattar et al, 2015). Accordingly, we propose the following hypotheses:…”
Section: Training and Development And Employee Satisfaction And Reten...mentioning
confidence: 99%
See 1 more Smart Citation